Qualitative Research Analysis in the area of Library and Information Science: (1981-2010) - Morena de Diago, Beatriz (Revista General de Información y Documentación, 2013)
The results of a study of production of Qualitative Research in the area of Library and Information Science are presented. It analyses the sources of publications that concentrate more contributions, the years and the language of this contributions and the geographical and institutional affiliation of the authors of the research articles retrieved in the databases Lisa (Library and Information Science Abstracts) and Lista (Library, Information Science & Technology Abstracts), with special emphasis on the particular analysis of the Spanish case. It includes a proposal for systematization of qualitative data collection techniques more recurrent in the literature: conversational techniques, documentation techniques and observational techniques.
Keywords: Qualitative Research; Library and Information Studies; Scientific Production; Data Collection; Qualitative Techniques.